Penundaan Kewajiban Pembayaran Utang dan Perdamaian pada Perseroan Terbatas Sebagai Upaya Perlindungan Debitor - Dadang Firdaus (Universitas Jayabaya, 2016)
the requirements of bankruptcy put the debtors vulnerable of insolvent exposure due to among other things broad definition of debt legal terminology in Law no 37 year 2004 on Bankruptcy and Suspension of Payment; absence of nominal limitation of debt for filing bankruptcy petition; stop payment is deemed as inability to settle debt to only two creditors not necessarily in insolvent state or unable to pay to all creditors